2002
DOI: 10.1086/342000
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Behavioral Variation in Estivation among Mud Turtles (Kinosternonspp.)

Abstract: Kinosternid mud turtles, a primarily aquatic group, exhibit variable degrees of terrestrial activity in the Sonoran and Chihuahuan Deserts. We compared behavioral and physiological responses to dry conditions in four populations representing three species, Kinosternon sonoriense, Kinosternon flavescens, and Kinosternon hirtipes. All four groups were subjected to simulated dry season conditions in the laboratory, during which activity was monitored and physiological responses (blood chemistry and rates of resti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…Although specialization of different phenotypes on different habitat types has been demonstrated in some birds (Ebenman and Nilsson 1982), and evidence for individual diet specialization has been found in lizards (Lister 1976) and in some snails (West 1986), there are still large knowledge gaps regarding individual specialization and its effects on resource selection. Variation in behaviour between populations (Ligon and Peterson 2002;Rees et al 2009) and within populations (Roe and Georges 2008) has been shown to be important in some turtle species and may represent physiological constraints, heritable traits, and (or) behavioural plasticity in response to environmental factors. Resource selection may also undergo ontogenetic shifts (Stamps 1983;Lind and Welsh 1994) or differ between the sexes (Ardia and Bildstein 1997;Bull 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although specialization of different phenotypes on different habitat types has been demonstrated in some birds (Ebenman and Nilsson 1982), and evidence for individual diet specialization has been found in lizards (Lister 1976) and in some snails (West 1986), there are still large knowledge gaps regarding individual specialization and its effects on resource selection. Variation in behaviour between populations (Ligon and Peterson 2002;Rees et al 2009) and within populations (Roe and Georges 2008) has been shown to be important in some turtle species and may represent physiological constraints, heritable traits, and (or) behavioural plasticity in response to environmental factors. Resource selection may also undergo ontogenetic shifts (Stamps 1983;Lind and Welsh 1994) or differ between the sexes (Ardia and Bildstein 1997;Bull 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they are confirmed to make behavioral use of the physiological capacity for estivation that has been demonstrated in the laboratory (Peterson and Stone, 2000;Ligon and Peterson, 2002). All animals equipped with radiotransmitters engaged in terrestrial estivation during the study, all were estivating at the onset of the rainy season, and all returned to the aquatic environment within a few days of the onset of the rainy season.…”
Section: Discussionmentioning
confidence: 64%
“…Because water is periodically unavailable during periods of drought, Stone (2001) also hypothesized that K. sonoriense engaged in terrestrial estivation to survive drought. Simulated estivation trials in the laboratory revealed that K. sonoriense is capable of surviving many weeks without food and water (Peterson and Stone, 2000;Ligon and Peterson, 2002). The response of K. sonoriense to such conditions was similar to K. flavescens, a welldocumented terrestrial estivator (Seidel 1978;Iverson, 1990), treated identically (Peterson and Stone, 2000;Ligon and Peterson, 2002).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations